Gill diseases in carps a Kolleru lake perspective - Pauland, Anirban; Sahoo, P K (Indian Farming, 2018)
The intensive fish farming practices since many years in poud polyculture system have led to fish being affected by different diseases including thoseÂ  of gill associated nature. The gill diseases are not only limited to the mostly cultured Indian major carp species, but also seen in catfish species, theÂ  second most cultured fish in that region.